(Table S1) Neogene temperature reconstruction of ODP Site 202-1241 - Osamu Seki; Daniela N Schmidt; Stefan Schouten; Ellen C Hopmans; Jaap S Sinninghe Damsté; Richard D Pancost (PANGAEA, 2012)
To examine the Late Neogene evolution of tropical Pacific oceanography, we determined multiple geochemical proxy records for temperature (UK37 extquotesingle and TEX86H indices) and primary productivity (algal biomarkers and diol indices) in sediments recovered at ODP Site 1241 in the East Equatorial Pacific (EEP) spanning a record of the last 10 Myr. The TEX86H temperatures are lower than those recorded by UK37 extquotesingle indices, exhibiting large fluctuations and suggesting strong warming during the Mid Pliocene Warm Period (MPWP; 4.5-3.2 Ma) and significantly colder temperature during the Late Miocene cooling period (7-5 Ma) and after the Middle Pliocene Warm Period (MPWP). Such variations could reflect changes in the EEP thermocline temperatures, but we suggest that they instead reflect changes in the depth of export production of glycerol dialkyl glycerol tetraether lipids in response to changes in the upper ocean structure. A combination of temperature records, inferred to represent different and likely varying depths in the water column, as well as algal biomarker records for export production and ecosystem structure, suggest that both productivity and inference upwelling were reduced in the EEP during warmer periods, such as the MPWP and prior to 7 Ma. In contrast, stronger upwelling conditions and associated increased productivity likely prevailed from 7 to 5 Ma and for the past 3 Myr, both corresponding to globally cool intervals. A further increase in EEP productivity occurred at ca 1.8 Ma, coincident with the development of the E-W Pacific SST gradient. These results confirm previous work that protracted El Niño-like conditions prevailed during warmer intervals of the Pliocene before ultimately descending into the current climate state.
Supplement to: Seki, O et al. (2012): Paleoceanographic changes in the Eastern Equatorial Pacific over the last 10 Myr. Paleoceanography, 27(3), PA3224, https://doi.org/10.1029/2011PA002158